Examples of superconducting technology application: sensing and interfacing - Kunert, J.; Ijsselsteijn, R.; Il‘ichev, E.; Brandel, O.; Oelsner, G.; Anders, S.; Schultze, V.; Stolz, R.; Meyer, H.-G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Technological processes for the fabrication of low- and high-Tc Josephson junctions, aimed for certain appli-cations, are described. On the one hand, the integration of low-Tc superconductor digital electronics with superconducting sensor arrays enables input signal processing with quantum limited resolution at millikelvin temperatures. We describe this mixed signal superconductor technology for analogue sensor readout and signal multiplexing for operating temperatures down to 300 mK. On the other hand, by making use of modern high-Tc Josephson junction technology, sensitive magnetometers, which require a modest cooling power, can be developed. Examples of the application of the mentioned processes are shown.